Infectious keratitis following photorefractive keratectomy: a 13-year study at a tertiary center - Alireza Attar; Hossein Jamali; Julio Ortega-Usobiaga; Golnoush Mahmoudinezhad; Dagny Zhu; Mohammad Mohammadi (Journal of Ophthalmic Inflammation and Infection)
Abstract Introduction Infectious keratitis is a rare but devastating complication following photorefractive keratectomy (PRK) that may lead to visual impairment. This study assessed the clinical features, treatment strategies, and outcomes of post-PRK infectious keratitis. Methods This retrospective study was conducted on patients with post-PRK infectious keratitis presenting to Khalili Hospital, Shiraz, Iran, from June 2011 to March 2024. The study was conducted in two stages: the first stage assessed the incidence of post-PRK infectious keratitis among patients who underwent PRK at our center, while the second stage included all patients with post-PRK infectious keratitis, regardless of where their PRK was performed. The following data were collected: demographics, post-surgery presentation time, risk factors, culture results, treatments, follow-up duration, complications, and corrected distance visual acuity (CDVA) at admission and the last follow-up. Results Forty-two patients (42 eyes) with a mean age of 28.74 years (male-to-female ratio of 1.2:1) were included. Among 38,938 PRK procedures performed at our center, the incidence of keratitis was estimated to be 0.018% (7/38,938). The odds of keratitis during the COVID-19 pandemic were 7.05 times higher (95% CI: 1.58 to 31.52, p-value = 0.015) than outside this timeframe (February 2020 to August 2023). Gram-positive bacteria were the most commonly isolated pathogens in microbiological studies, accounting for 45.2% (19/42) of cases. Early-onset infections were primarily caused by Staphylococcus aureus (9/26, 34.6%), Staphylococcus epidermidis (4/26, 15.4%), and Pseudomonas aeruginosa (4/26, 15.4%), whereas all of the cases with fungi (4/4, 100% (and Acanthamoeba (3/3, 100%) infections caused late-onset infections. All patients received broad-spectrum antibiotic therapy, followed by adjusted treatment based on microbial results. Cases developing endophthalmitis and those not responding to treatment or having non-resolving corneal scars required further interventions, such as penetrating keratoplasty and deep vitrectomy. The mean follow-up duration was 40.81 months, and 97.6% (41/42) of cases experienced CDVA improvement at follow-up. Conclusion This long-term study found a post-PRK keratitis rate of 0.018%, with gram-positive bacteria as the most common pathogens. Prompt management and regular follow-up assessments are essential for achieving satisfactory outcomes.